Personality Traits and Further Training - Marie-Christine Laible; Silke Anger; Martina Baumann (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2020)
The notion of lifelong learning is gaining importance, not only in the labor market but also in other areas of modern societies. Previous research finds variation in occupation-related training participation by worker and workplace characteristics, gender, and education. However, evidence on the individual's socio-emotional skills creating favorable conditions for overall further training is scarce. To close this research gap, we analyze the role of personality for further training participation. First, we compare how the Big Five Personality Dimensions relate to different training types by differentiating between non-formal and informal training measures. Second, we investigate how personality traits affect further training chosen for occupational and private reasons separately. Drawing on a sample of 10,559 individuals from the Adult Stage of the German National Educational Panel Study (NEPS), we find that throughout our estimations, openness to experience positively relates to further training participation and is the most important determinant among the Big Five Personality Dimensions. However, the relationship between personality traits and training participation varies according to the training type and the reason for participating in further training. Moreover, we find gender-specific differences in the association between personality traits and lifelong learning. We conclude that personality is an important predictor of lifelong learning decisions. – – Lebenslanges Lernen wird nicht nur für den Arbeitsmarkt, sondern auch für andere Lebensbereiche moderner Gesellschaften immer relevanter. Bisherige Studien finden einen Zusammenhang zwischen beruflicher Weiterbildung und Arbeitnehmer-, sowie Arbeitgebermerkmalen, Geschlecht und Bildung. Jedoch gibt es bisher kaum Evidenz für die Bedeutung individueller sozio-emotionaler Fähigkeiten für die allgemeine Weiterbildungsteilnahme. Um diese Forschungslücke zu schließen, untersuchen wir den Zusammenhang zwischen Persönlichkeitseigenschaften und der Teilnahme an Weiterbildungen. Dabei vergleichen wir zunächst die Rolle der Big Five Persönlichkeitseigenschaften für unterschiedliche Formen der Weiterbildung, non-formale und informelle Weiterbildung, und unterscheiden dann zwischen einer Teilnahme an beruflicher und an privater Weiterbildung. Auf Basis von 10.559 Befragungspersonen der Erwachsenenbefragung des Nationalen Bildungspanels (NEPS) können wir zeigen, dass Offenheit für neue Erfahrungen in allen Schätzungen positiv mit der Weiterbildungsteilnahme zusammenhängt. Offenheit für neue Erfahrungen ist damit die wichtigste Persönlichkeitseigenschaft im Kontext des lebenslangen Lernens. Die Rolle der restlichen untersuchten Persönlichkeitseigenschaften hängt von der Form der Weiterbildung (non-formal vs. informell) und der Motivation für die Teilnahme (privat vs. beruflich) ab. Des Weiteren finden wir geschlechtsspezifische Unterschiede im Zusammenhang zwischen Persönlichkeitseigenschaften und lebenslangem Lernen. Wir folgern, dass Persönlichkeitseigenschaften ein wichtiger Prädiktor der Bildungsentscheidung für lebenslanges Lernen sind.
Keywords: D91; J24; M53; 330; Big Five personality traits; continuing education; further training participation; lifelong learning; NEPS; socio-emotional skills